Toponymy of Herschel island (Qikiqtaryuk), Western Arctic Coast, Canada - Burn, C. (Christopher R.); Hattendorf, J.B. (John B.) (ARCTIC, 2011)
The official names for several of the features on Herschel Island are derived from the visit to the island by USS Thetis, Lt. Cdr. Charles Stockton commanding, on 15-16 August 1889. In 24 hours, Stockton and his crew surveyed the coast sufficiently to compile and publish a map, which included the bathymetry of Pauline Cove and the strait between the island and the mainland, now called Workboat Passage. Stockton named features after two whaling ships that were in the vicinity when he arrived (Orca and Thrasher), his own Thetis, his wife (Pauline Lethilhon King), three ensigns to whom he assigned bathymetric surveys (Robert Lopez, Edward Simpson, and Rogers Wells, Jr.), two of his other officers (Lt. Arthur Osborn and Ensign John Bell), and an officer of the Royal Navy (Capt. Sir Richard Collinson). Only one feature, Avadlek Spit, has an Inuvialuktun official name.